2020
DOI: 10.3389/fmicb.2020.01602
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus megaterium WL-3 Lipopeptides Collaborate Against Phytophthora infestans to Control Potato Late Blight and Promote Potato Plant Growth

Abstract: Oomycete Phytophthora infestans [(Mont.) de Bary] is the cause of potato late blight, a plant disease which poses a serious threat to our global food security and is responsible for huge economic losses worldwide. Lipopeptides produced by Bacillus species are known to be potent antibacterial compounds against many plant pathogens. In this study, we show that Bacillus megaterium WL-3 has an antagonistic effect against potato late blight. Elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…The mass spectrum peaks of them corresponded to the ion addition peaks of C16 Fengycin A, C16 Fengycin C, and C16 Fengycin D ( Table 4 ). The results were similar to those of Youyou Wang [ 36 ] and Bo Zhang [ 37 ]. These results indicated that strain E2 could produce two LPs; Iturin and Fengycin.…”
Section: Resultssupporting
confidence: 89%
“…The mass spectrum peaks of them corresponded to the ion addition peaks of C16 Fengycin A, C16 Fengycin C, and C16 Fengycin D ( Table 4 ). The results were similar to those of Youyou Wang [ 36 ] and Bo Zhang [ 37 ]. These results indicated that strain E2 could produce two LPs; Iturin and Fengycin.…”
Section: Resultssupporting
confidence: 89%
“…Another important mechanism by Bacillus for suppressing plant pathogens is the production of antifungal metabolites and antibiotics [41][42][43][44][45]. The biocontrol fungus Chaetomium globosum is effective in inhibiting B. sorokiniana associated with wheat common root rot owing to the production of secondary metabolites by C. globosum [16].…”
Section: Discussionmentioning
confidence: 99%
“…Bacillomycin L and Fengycin A compounds were isolated from strain G341, which controlled the development of rice blast, sheath blight, tomato gray mold and red pepper anthracnose [47]. Lipopeptides from Bacillus megaterium strain WL-3 containing three subfamilies, surfactant, Iturin A and Fengycin A, which control late blight and promote potato plant growth [43]. In our opinion, it is necessary to assay and evaluate the lipopeptide of XZ34-1 in the future to further explore its mechanism of action and broaden its application.…”
Section: Discussionmentioning
confidence: 99%
“…Fengycin and surfactin have been reported to enhance the expression of glucanase and peroxidase genes in mandarin fruit (Waewthongrak et al 2014). While, fengycin A and iturin A presented the potency of plant photosynthesis involving in plant growth promotion (Wang et al 2020). In addition, Bacillus CLPs were reported the ability to increase seed germination and plant growth promotion in chili pepper, lettuce, tomato, and pea (Umar et al 2021).…”
Section: Introductionmentioning
confidence: 99%